(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Ramipril being ACE inhibitor belongs to BCS class II drug with low solubility and undergoes first-pass metabolism that leads to reduced bioavailability of 28%. The current research is aimed at formulating and evaluating ramipril fast dissolving oral films (FDOF). Solubility enhancement of ramipril was done by formation of inclusion complex with β-cyclodextrin in 3 ratios (1:0.5, 1:1, 1:2). Based on higher drug content and dissolution values the physical mixture of ramipril with β-cyclodextrin in 1:1 ratio (IC2) was chosen for further studies. Total 12 formulations of ramipril FDOF containing IC2 prepared with various polymers and evaluated for physicochemical properties. The optimized formulation F9 shown better tensile strength (11.6 g/cm2), significant % elongation (9.8) and maximum % drug content of 99.98 %. The formulation F9 exhibited minimum disintegration time of 9 sec that is desirable for immediate onset of action and maximum drug release. The FTIR data of F9 assured the compatibility of drug and formulation excipients, found to be stable for 180 days at accelerated conditions. The study confirmed that ramipril FDOF lead to quicker onset of action and enhanced therapeutic efficiency in comparison to marketed product.